Delivery Mode and the Pelvic Floor Function of Primiparous Women at Early Postpartum: An Observational Retrospective Cohort Study - Xiaolei Chi; Lin Wen; Lan Chen; Hongxia Zhu (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Different modes of delivery are strongly associated with postpartum pelvic floor muscle (PFM) injury and postpartum pelvic floor dysfunction. This study used Glazer PFM surface electromyography (sEMG) to objectively assess postpartum PFM function to determine the effects of different modes of delivery on pelvic floor function in the early postpartum period in primiparous women. Methods: There were 1286 cases of cesarean delivery (CD) and 2099 cases of vaginal delivery (VD). The vaginal delivery group was further divided into four subgroups (A: intact perineum without laceration and first-degree laceration; B: second-degree laceration; C: mediolateral episiotomy; D: forceps delivery). Pelvic floor sEMG indices of the subjects were analyzed at 6–8 weeks postpartum. Results: The results showed that the mean peak amplitude of phasic (flick) contractions and the mean amplitude of tonic contractions were both significantly higher in CD than in VD (p < 0.01). In contrast, the mean amplitude variability of tonic contractions was lower in CD than in VD (p < 0.01). The mean peak amplitude of phasic (flick) contractions and the mean amplitude of tonic contractions were statistically lower in the forceps group than in the other vaginal delivery groups (p < 0.05). The mean amplitude variability of tonic contractions was greater in the forceps group than in groups A, B and C (p < 0.01). Conclusions: Vaginal delivery, especially forceps delivery, may result in impaired pelvic floor muscle function in the early postpartum period compared to cesarean delivery.